Vision-Related Quality of Life in Patients With Atypical Optic Neuritis - Jiang, Zhaocai; Qian, Haiyan; Wei, Shihui (Frontiers in Pain Research, 2022)
Abstract AIM: To evaluate vision-related quality of life in patients with atypical optic neuritis through the 39-item National Eye Institute Visual Function Questionnaire (NEI VFQ-39). METHODS: Fifty-seven patients with atypical optic neuritis were scheduled in the research unit from June 1 to December 31, 2019. Besides collecting the clinical data, NEI VFQ-39, the Chinese version, was applied to all subjects. The NEI VFQ-39 subscale item scores were compared among subgroups divided by different classifications, and correlation analysis of the NEI VFQ-39 scores and BCVA for better-seeing and worse-seeing eyes was performed. RESULTS: The mean age of scheduled patients was 34.3±12.4 years, with the majority being female (70.2%). The mean composite score was 58.62±17.62. Twenty-nine (50.9%) patients were affected binocularly, and the most subscale scores and composite score of binocular incidence were lower than those of monocular incidence significantly. But there was no statistically significant difference in composite scores between patients with and without periocular pain. The patients with worse BCVA in the better-seeing eye have lower scores than those with better BCVA in better-seeing eye. Most NEI VFQ-39 scores have strong correlations with the BCVA for better-seeing and worse-seeing eyes. CONCLUSION: Atypical optic neuritis has significant and comprehensive influence on patients’ visual function outcomes and quality of life associate with vision. Improving their BCVA in the better-seeing eye can improve their vision-related QOL.